A new species of African snake-eyed skink (Scincidae: Panaspis) from central and northern Namibia - Ceríaco, Luis M. P.; Branch, William R.; Bauer, Aaron M. (Zootaxa, 2018)
A recent molecular revision of the snake-eyed skinks of the genus Panaspis Cope, 1868 uncovered extensive cryptic diversity within the P. wahlbergi (Smith, 1849) and P. maculicollis Jacobsen & Broadley, 2000 species complexes. We here describe an unnamed central and northern Namibian lineage of the P. maculicollis group as a new species. We base the description on previously published molecular evidence and newly collected morphological, meristic and coloration data. Members of the group share a conservative morphology and the newly described species is very similar to P. maculicollis, from which it differs mostly on the basis of its coloration. This description raises the number of Panaspis recognized to 17 species and reinforces the already strong evidence that northern Namibia is a hotspot of reptile diversity.